Literature as a Cross Cultural Communication Media by Andrea Hirata’s Edensor Novel in BIPA Learning - Nur Syamsi Rafsanjani Almakali; Oktavia Winda Lestari; Mohamad Jazeri (Bulletin of Social Studies and Community Development, 2024)
Abstract: Literature is considered as a medium of cross-cultural communication that can lead to the existence of a culture in a new environment. Literature used as a medium of cross-cultural communication can be a tool for BIPA learning. The purpose of this study is to describe the existence of cross-cultural communication through literature in BIPA learning. The data of this research are in the form of depictions of events experienced by characters in literature. The data obtained were then analyzed by interpreting, described and then analyzed. The analysis was carried out in an analytical descriptive way through the reading of literary works. The data collection technique used is a literature study by collecting qualitative data from previous studies and relevant theories in accordance with the theme of the study. The results of this study prove that Andrea Hirata's Edensor novel represents persistence with culture and as a medium of cross-cultural communication in BIPA learning. Based on the results of the study, it can be concluded that the cross-culture described in Edensor's novel is due to the persistence of an indigenous child's dream in a new environment.    Keywords: literature, communication media, cross culture, novel, edensor.